Treatment and compliance with virtual reality and anaglyph‐based training programs for convergence insufficiency. (22nd March 2020) - Boon, Mei Ying; Asper, Lisa J; Chik, Peiting; Alagiah, Piranaa; Ryan, Malcolm
Abstract : Background: Convergence insufficiency may be treated by visual exercises designed to increase convergence while maintaining single, clear, binocular vision. However, compliance with treatment is problematic, as patients often cease treatment when symptoms start to improve and before treatment is complete. The purpose of the present study was to assess the feasibility of using gamification of vision training to: (a) treat convergence insufficiency; and (b) improve compliance to treatment in comparison to a conventional treatment over a six‐week treatment period. Methods: Two interventions, anaglyphs and a virtual reality game of Snakes, were evaluated for their effectiveness in treating adults with convergence insufficiency. The prescribed training regimen was 20 minutes, three times per week for six weeks. Vision was assessed before and after the treatment period. Participants also filled in the Core Elements of the Gaming Experience Questionnaire to gauge impact of game design on compliance. Results: Eighteen participants (mean age 20.8 ± 1.8 years) met the inclusion criteria for convergence insufficiency and nine participants were randomly assigned to each intervention. Repeated measures analysis of variance showed a significant effect of visit for near point of convergence (F1, 16 = 38.32, p < 0.0001), near positive fusional reserves break (F1, 16 = 21.94, p < 0.0001) and recovery (F1, 16 = 26.87, p < 0.0001), but not of intervention type. Total time played was significantly longer for the virtual reality Snake Game than the anaglyph intervention (p < 0.0001), which translated to mean compliance of 82 per cent and 51 per cent respectively. Conclusion: Gamification of vision training in a virtual reality environment is feasible and associated with increased compliance, hence may be a useful strategy to treat convergence insufficiency.